Perancangan Aplikasi E-Tourism untuk Mendukung Pariwisata Kota Padang - Faradika; Zulfahmi; Renita Astri (Prosiding SISFOTEK, 2020)
Padang City, West Sumatra Province, is one of the regions in Indonesia that has a good tourism and cultural sector. However, in the dissemination of information about tourism in the city of Padang has not been fully optimal carried out by the City Government of Padang. The community is not fully aware of tourist attractions in the city of Padang. Based on this reason the author designed an E-Tourism Application to Support Padang City Tourism Based on Android. The author analyzes and designs applications that are built using the SDLC (Systems Development Life Cycle) method with the stages of system requirements analysis and system modeling design using the UML method. For programming languages the author uses PHP, Java on Android Studio and MySQL Database. From this study produced an Android-based E-Tourism application that is integrated with the display of tourist locations on google maps as well as features adding tourist rating.